2022
DOI: 10.1186/s12893-022-01869-5
|View full text |Cite
|
Sign up to set email alerts
|

Residual cancer is a strong predictor of survival in T3 incidental gallbladder cancer

Abstract: Background and purpose Index cholecystectomy is insufficient for curing T3 incidental gallbladder cancer (IGC), and once residual cancer (RC) is found, the prognosis is often poor. The purpose of this study was to investigate the effect of RC on the prognosis and the optimal choice of adjuvant therapy for R0 reresection patients with T3 IGC. Methods We retrospectively reviewed data from patients with T3 IGC who underwent radical reresection from Ja… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…A total of 3 studies 50 , 52 , 55 with 617 cases were incorporated. Pooled results indicated that hepatic tumor shared more worse prognosis than peritoneal tumor and tumor location (peritoneal side vs hepatic side) was a prognostic factor for resected GBC (HR=1.85, 95% CI: 1.51–2.28, P <0.00001) (Figure S1L, Supplemental Digital Content 4, http://links.lww.com/JS9/C302 ) (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 3 studies 50 , 52 , 55 with 617 cases were incorporated. Pooled results indicated that hepatic tumor shared more worse prognosis than peritoneal tumor and tumor location (peritoneal side vs hepatic side) was a prognostic factor for resected GBC (HR=1.85, 95% CI: 1.51–2.28, P <0.00001) (Figure S1L, Supplemental Digital Content 4, http://links.lww.com/JS9/C302 ) (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 20 studies 9 , 17 , 23 , 28 , 32 , 35 , 36 , 38 , 41 , 44 , 46 49 , 51 55 , 57 with 3864 cases were incorporated. Pooled results indicated that positive margin was a risk factor for OS among resected GBC (HR=2.90, 95% CI: 2.42–3.47, P <0.00001) (Figure S1N, Supplemental Digital Content 4, http://links.lww.com/JS9/C302 ) (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation